ORGANIZATIONAL COMMITMENT STUDY AT PT. BAS: EFFECTS OF WORKLOAD - Puspita Puji Rahayu (Pusat Riset dan Inovasi Nasional, 2021)
This study intends to investigate how workload at PT. Bandung Prosperous Administration Development affected organizational commitment. The study's sample consisted of 111 employees of PT. Bandung Prosperous Administration Development. Choosing the study's sample through saturated sampling. The method of analysis is multiple linear regression. The results of the investigation show that being busy has a considerable, unfavorable impact on job satisfaction. Job satisfaction has a considerable and positive influence on organizational commitment.